Measurement of Chromosomal Arms and FISH Reveal Complex Genome Architecture and Standardized Karyotype of Model Fish, Genus Carassius - Knytl, Martin; Fornaini, Nicola Reinaldo (Cells, 2021)
The widely distributed ray-finned fish genus Carassius is very well known due to its unique biological characteristics such as polyploidy, clonality, and/or interspecies hybridization. These biological characteristics have enabled Carassius species to be successfully widespread over relatively short period of evolutionary time. Therefore, this fish model deserves to be the center of attention in the research field. Some studies have already described the Carassius karyotype, but results are inconsistent in the number of morphological categories for individual chromosomes. We investigated three focal species: Carassius auratus, C. carassius and C. gibelio with the aim to describe their standardized diploid karyotypes, and to study their evolutionary relationships using cytogenetic tools. We measured length (q+plength) of each chromosome and calculated centromeric index (i value). We found: (i) The relationship between q+plength and i value showed higher similarity of C. auratus and C. carassius. (ii) The variability of i value within each chromosome expressed by means of the first quartile (Q1) up to the third quartile (Q3) showed higher similarity of C. carassius and C. gibelio. (iii) The fluorescent in situ hybridization (FISH) analysis revealed higher similarity of C. auratus and C. gibelio. (iv) Standardized karyotype formula described using median value (Q2) showed differentiation among all investigated species: C. auratus had 24 metacentric (m), 40 submetacentric (sm), 2 subtelocentric (st), 2 acrocentric (a) and 32 telocentric (T) chromosomes (24m+40sm+2st+2a+32T); C. carassius: 16m+34sm+8st+42T; and C. gibelio: 16m+22sm+10st+2a+50T. (v) We developed R scripts applicable for the description of standardized karyotype for any other species. The diverse results indicated unprecedented complex genomic and chromosomal architecture in the genus Carassius probably influenced by its unique biological characteristics which make the study of evolutionary relationships more difficult than it has been originally postulated.
Keywords: karas zlatý; Male; Chromosome Mapping; chromozomy; Carassius carassius; karyotypizace; karyogram; genetická variace; hybridizace in situ fluorescenční; fylogeneze; Phylogeny; Karyotyping; kapři; karyotyp; i value; mužské pohlaví; chromosome; ryby; Carassius auratus; Fishes; genom; Animals; ženské pohlaví; Chromosomes; mapování chromozomů; Goldfish; zvířata; Carps; Diploidy; In Situ Hybridization, Fluorescence; Genome; Polyploidy; Carassius gibelio; Genetic Variation; in situ hybridization; Female; diploidie; q/p arm ratio; Karyotype; polyploidie